The study of the life in Zubiri: a brief route from his first extrauniversity courses to Sentient Intelligence - Vargas Abarzúa, Esteban (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper attempts to show the central scheme by which Zubiri presented his conception about life from his first extrauniversity courses to Sentient Intelligence. This scheme presents life in three strata intrinsically related called «arousal-tonic modification-response», «habit-formal respect» and «structure of life». These strata are ordered from most superficial to deeper in the founding order. In addition, Zubiri presents a radical unitary idea of life that qualifies as «auto-possession». It is his idea of life like mode of reality that, somehow, tell us the essential of the three strata mentioned above. On the other hand, in this work we tried to rethink all this scheme of life from his great work called Sentient Intelligence. Based in that work, we hold that the founding order must be reversed. What was presented as more radical is now less accessible to an analysis of mere facts obtained from the human apprehension.
Keywords: life; Zubiri; auto-possession; vital action; habit; structure